Clinical and Enzymatic Evaluation of Liver Function in Patients with Chronic HBV Infection - Zhazan Najat Jabbar (American Journal of Biology and Natural Sciences, 2026)
This study aimed to assess clinical and enzyme variation in hepatitis B virus (HBV)- related liver function in chronically infected patients by comparing findings with those of a control group of healthy individuals. A total of 60 patients, 30 having chronic HBV and 30 healthy individuals as a control group, were sampled. The methodology involved collecting clinical information through direct patient interviews, focusing on typical symptoms such as fatigue, loss of appetite, jaundice, and upper right quadrant abdominal pain. Physical examination was also performed to assess liver size and determine whether there was fibrosis or hepatomegaly. The automated analyses from the Mindray BS-240 were subsequently used in the laboratory to measure liver enzymes, including ALT, AST, ALP, and GGT. Also, levels of total and direct bilirubin, as well as total protein and albumin, were determined. HBsAg testing was also performed on all samples to confirm chronic infection. Medical interviews of the patients provided clinical data, with general fatigue (83.3%), loss of appetite (70%), jaundice (40%), and upper right quadrant pain as the most noticeable symptoms. Also, 60% of cases were characterised by hepatomegaly, suggesting that the virus directly affected overall health and liver function. As for laboratory tests, liver enzymes (ALT, AST, ALP, GGT) were significantly increased in the patient group, with highly significant differences (P < 0.001). For example, the average ALT level of the patients was 85.4 ± 22.7 U/L, compared with 28.1 ± 6.5 U/L in the control group. In addition, total and direct bilirubin were markedly elevated, whereas albumin and total protein were decreased, indicating impaired hepatic synthetic function. This study confirms the fact that chronic HBV causes a number of liver function disturbances, which are evident and reflected both in clinical manifestations and in laboratory results. Regular evaluation of these signs is very important to prevent the development of disease and complications such as fibrosis or even liver cancer. The study also recommends extending routine screening in areas with a high prevalence of infection, improving health awareness campaigns, and promoting early diagnosis as an essential pillar of management and surveillance for this disease.